The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/annrheumdis-2020-eular.346
|View full text |Cite
|
Sign up to set email alerts
|

Op0231 comparative Effectiveness of Jak-Inhibitors, TNF-Inhibitors, Abatacept and Il-6 Inhibitors in an International Collaboration of Registers of Rheumatoid Arthritis Patients (The “Jak-Pot” Study)

Abstract: Background:In many countries, JAK-inhibitors (JAKi) have only recently been approved as treatment for patients with rheumatoid arthritis (RA).Objectives:To evaluate the effectiveness of JAKi compared to bDMARDs in RA patients in the real-world population in an international collaboration of registers (the “JAK-pot” collaboration).Methods:Patients initiating either JAKi, TNFi, IL-6i or abatacept (ABA) during a time period when JAKi were available in each country (19 registers, Table) were included. We compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…During the observation period, the proportions of patients receiving monotherapy were 50.9% and 31.2% for baricitinib-treated patients and patients treated with another tsDMARD or any bDMARD, respectively. This finding is aligned with the findings of the JAK-POT study, which evaluated the effectiveness of JAK inhibitors compared with bDMARDs in patients with RA initiating treatment with these agents in the usual care, using data from 17 international registries [ 32 ]. This study reported that JAK inhibitors were more often initiated as monotherapy than were bDMARDs.…”
Section: Discussionsupporting
confidence: 72%
“…During the observation period, the proportions of patients receiving monotherapy were 50.9% and 31.2% for baricitinib-treated patients and patients treated with another tsDMARD or any bDMARD, respectively. This finding is aligned with the findings of the JAK-POT study, which evaluated the effectiveness of JAK inhibitors compared with bDMARDs in patients with RA initiating treatment with these agents in the usual care, using data from 17 international registries [ 32 ]. This study reported that JAK inhibitors were more often initiated as monotherapy than were bDMARDs.…”
Section: Discussionsupporting
confidence: 72%
“…Further studies are now required to refine and validate OPEX. For example, future research will enable further comparisons in newer trials, such as the recent RCT comparing a Jak inhibitor to a TNFi-in which the former was found to be more effective but at a higher risk of toxicity [11]. Other notable examples include high risk decisions in which the patient experience is markedly different between two options, such as early rhythm control versus usual care for atrial fibrillation.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…A real-world study of more than 25,000 patients with RA found that the hazard ratio for drug discontinuation tended to be lower for JAK inhibitors than for TNF inhibitors. 13 However, discontinuation rates were comparable for the JAK inhibitors, abatacept, and specific IL-6 inhibitors. 13 Further investigation is needed to determine the key factors influencing drug discontinuation in patients with RA and whether or not the route of treatment administration plays a role.…”
Section: Rheumatoid Arthritismentioning
confidence: 96%
“…13 However, discontinuation rates were comparable for the JAK inhibitors, abatacept, and specific IL-6 inhibitors. 13 Further investigation is needed to determine the key factors influencing drug discontinuation in patients with RA and whether or not the route of treatment administration plays a role. In 3 decades, scientific advancements have led to the evolution of the RA therapeutic landscape from general immunosuppressants to targeted biological and synthetic DMARDs.…”
Section: Rheumatoid Arthritismentioning
confidence: 96%